MECHANISMS AND INSTRUMENTS FOR PROMOTING OF INTERMUNICIPAL ECONOMIC COOPERATION IN TERRITORIALCOMMUNITIES OF UKRAINE (Regional aspects of productive forces development of Ukraine, 2022)
Introduction. The article considers the scientific principles of solving the problem of intensifying of territorial communities cooperation in the field of economic development based on the use of mechanisms and tools of financial, budgetary, organizational, informational stimulation of communities cooperation, according to their specialization advantages, prerequisites for building and improving of horizontal links.Goal of the article is to identify scientifically substantiated measures to stimulate economic development and cooperation of communities in Ukraine using mechanisms and tools of financial, economic, tax, organizational, information support for joint participation in the inter-territorial division of labor.Research methods: for the solving of the problem methods of statistical, logical, systematic analysis are used to identify the causes of changes in the dynamics of cooperation agreements of communities, and the method of synthesis of mechanisms and tools to enhance cooperation of local communities in economic development are also used.Results. The assessment of institutional support, dynamics and structure of territorial communities cooperation in Ukraine is carried out and the tendency of increase and gradual decrease of activity of their cooperation is revealed. Referring to the international experience of community cooperation, it is established that with the help of inter-municipal cooperation it is possible to ensure the socio-economic development of territorial and economic systems on the basis of their joint implementation of investment, social-economic projects. It is also substantiated the necessity of creating of objective conditions for the increasing of interest of communities in the implementation of economic cooperation, the development of which in the territorial communities of Ukraine is still quite low, The mechanism of stimulating of economic development and cooperation of communities in Ukraine with the use of tools for financial cooperation, by improving the existing system of horizontal equalization of territorial communities capacity, using  resources of national regional development funds, European support programs, as well as tax instruments to stimulate cooperation, including such local tax as land tax, the rates of which are to be differentiated depending on the passage of a particular project of inter-territorial economic cooperation payback stage. .Prospects for the study are seen in the further, deeper assessment of the effectiveness of the proposed mechanisms and tools of stimulation of economic cooperation of local communities from the standpoint of expanded interpretation of the concept of sustainable development, with economic, budgetary, social and environmental components.